Religion, Halal Logo, Extrinsic Halal Awareness in Influencing Muslim Attitudes Towards Halal Food - Nur Aida; Nur Sitti Khumairoh (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The research aims to analyze religious awareness and halal logos against extrinsic halal awareness and attitudes. Variable research consists of variable endogenous attitudes and extrinsic halal awareness as well as variable exogenous religiosity, and halal logo. The type of research is quantitative with a perverted instrument using the Likert scale. The study population was a Muslim community with a sample count of 161 with sampling techniques being judgment sampling. The analysis tool used is SEM AMOS. The results of the study are that consumer religion has a negative and insignificant influence on extrinsic halal awareness, a halal logo has a positive and significant influence on halal awareness, extrinsic religion has a positive and significant influence on attitudes. halal logos have a positive and significant influence on attitudes. extrinsic halal awareness has no significant and positive influence on attitudes